2012
DOI: 10.1002/hpm.2113
|View full text |Cite
|
Sign up to set email alerts
|

The provincial health office as performance manager: change in the local healthcare system after Thailand's universal coverage reforms

Abstract: This paper examines the implementation of Thailand's universal coverage healthcare reforms in a rural province, using data from field studies undertaken in 2003-2005 and 2008-2011. We focus on the strand of policy that aimed to develop primary care by allocating funds to contracting units for primary care (CUPs) responsible for managing local service networks. The two studies document a striking change in the balance of power in the local healthcare system over the 8-year period. Initially, the newly formed CU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…THPHs continued this policy by maintaining sites in rural locations convenient to local populations [49], and these rural THPHs were the ones likely to be staffed by public health officers (80.7% of sampled patients in THPH PH were employed in agriculture compared with lower figures for the other two types). The fact that THPH PHs tend to be away from urban centres probably explains why they rated higher for accessibility than the other two types.…”
Section: Discussionmentioning
confidence: 99%
“…THPHs continued this policy by maintaining sites in rural locations convenient to local populations [49], and these rural THPHs were the ones likely to be staffed by public health officers (80.7% of sampled patients in THPH PH were employed in agriculture compared with lower figures for the other two types). The fact that THPH PHs tend to be away from urban centres probably explains why they rated higher for accessibility than the other two types.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Establishment of regional outpost offices of the NHSO (2008NHSO ( -2011: by 2008, the control of budget had passed over to the NHSO from the MoPH, which then established regional outpost offices to manage distribution of funds to the primary care networks (Contracted Units for Primary Care or CUP). This resulted in a significant change in the role of the MoPH and the PHOs which shifted from a "command role" to "performance management role", providing oversight and review of CUP strategic and annual plans (Intaranongpai et al, 2012).…”
Section: Thailand Case Studymentioning
confidence: 99%
“…Sabatier (1999. P. 149) has written of the "desirability of longitudinal studies of a decade or more", and others have suggested that major health reform efforts may last for ten to twenty years (Intaranongpai et al, 2012;Al-Abri, 2019). Where there is an extended reform push as with UHC in Nigeria, we do not know whether it is more appropriate to theorize that a succession of policy windows open and close until an opportunity to complete implementation is taken, or if the problem for policy makers is to stretch a single window over a long time period.…”
Section: Future Research Recommendationsmentioning
confidence: 99%